2023
DOI: 10.1007/s10549-023-06915-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes on surgery and radiotherapy for breast cancer

Abstract: Purposes This study aims to examine whether diabetes has an impact on the use of surgery and adjuvant radiotherapy in treating women with localised breast cancer. Methods Women diagnosed with stage I–III breast cancer between 2005 and 2020 were identified from Te Rēhita Mate Ūtaetae—Breast Cancer Foundation New Zealand National Register, with diabetes status determined using New Zealand’s Virtual Diabetes Register. The cancer treatments examined included b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…Additionally, diabetes is associated with prolonged surgical delays, as indicated by an OR of 1.16 (95% CI: 1.05-1.27). 2 We also found that women with diabetes were less likely to have chemotherapy, but that women with diabetes were more likely to receive endocrine therapy for stage III disease and had better adherence to endocrine therapy. 13,14 The impact of diabetes on survival in people with breast cancer has not been examined in Aotearoa/New Zealand, and findings from international studies are controversial.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Additionally, diabetes is associated with prolonged surgical delays, as indicated by an OR of 1.16 (95% CI: 1.05-1.27). 2 We also found that women with diabetes were less likely to have chemotherapy, but that women with diabetes were more likely to receive endocrine therapy for stage III disease and had better adherence to endocrine therapy. 13,14 The impact of diabetes on survival in people with breast cancer has not been examined in Aotearoa/New Zealand, and findings from international studies are controversial.…”
Section: Introductionsupporting
confidence: 51%
“…Additionally, it contributes to prolonged delays in surgery for breast cancer patients. 2 Women with diabetes were also undertreated with chemotherapy, 28 but had better adherence to endocrine therapy than women without diabetes. 13,14 Nevertheless, this study indicates that despite observed treatment disparities between women with diabetes and those without, these differences did not translate into discernible disparities in breast cancer survival after adjustments for age and cancer stage.…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based study in New Zealand, women with diabetes with breast cancer had lower odds of radiotherapy following lumpectomy compared with counterparts without diabetes. 40 This difference was not significant after adjustment for comorbidity scores in addition to demographic The analysis of radiation therapy was restricted to patients undergoing breast-conserving surgery and node-positive patients undergoing mastectomy. Chemotherapy was analyzed in patients with nodepositive tumors and patients with hormone receptornegative tumors or hormone receptor-positive and ERBB2-positive tumors.…”
Section: Discussionmentioning
confidence: 98%
“…17 DM is linked to a reduced likelihood of undergoing mastectomy and a lower probability of receiving breast reconstruction postmastectomy. 18 Patients of older age, greater obesity, and higher comorbidity burden had a reduced likelihood of undergoing breast reconstruction. 18 These preoperative differences were observed in the DM patients in this study and may contribute to their lower rates of breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…18 Patients of older age, greater obesity, and higher comorbidity burden had a reduced likelihood of undergoing breast reconstruction. 18 These preoperative differences were observed in the DM patients in this study and may contribute to their lower rates of breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%